Perilaku Fraud Detection Pada Auditor: Professional Skepticism, Whistleblowing, Integritas, Time Pressure - Maya Piserah; Vanessa Fonda Sutjipto; Amrie Firmansyah; Estralita Trisnawati (Institut Bisnis dan Informatika Kesatuan, 2022)
This study examines the effect of professional skepticism, whistleblowing, integrity and time pressure on fraud detection. This study uses primary data to collect information in a questionnaire distributed online via a google form. The sample in this study were auditors who worked at KAP in Jabodetabek with 70 respondents based on random sampling—testing the hypothesis of this study using multiple linear regression analysis. This study indicates that professional skepticism does not affect fraud detection. Whistleblowing and integrity have a positive effect on fraud detection. Time pressure has a negative impact on fraud detection.